Analisis Butir Soal Tes Matematika Materi Trigonometri - M.M Endang Susetyawati; Wicaksono, Bintang (Jurnal Derivat: Jurnal Matematika dan Pendidikan Matematika, 2023)
In learning outcomes assessment activities, teachers play an active role in preparing measuring instruments. Competency measurement tools must have appropriate quality criteria used in measuring student competence. This study aims to determine the characteristics of the mathematical competency test instrument in terms of item validity, item difficulty level, item discriminating power and distractor function. The instrument developed is a competency test instrument for trigonometry material. The form of this instrument is multiple choice. The sample of this research is SMA Negeri 5 Yogyakarta. Analysis of the Trigonometry competency test items was carried out using qualitative analysis with the result that 85% in terms of material had good criteria, 82.5% in terms of construction had good criteria and 92.5% in terms of language had good criteria. Quantitative analysis of the Trigonometry competency test shows that 27 items (67.5%) have good validity, the test has a reliability value of 0.709 with good criteria. There were 26 questions (65%) with moderate difficulty level, 28 questions (70%) had good category discrimination, and 37 questions (92.5%) had good criteria for the distraction function.  Keywords:  validity, reliability, difficulty level, differentiating power